Vector wave propagation method - Fertig, Matthias Wilhelm; Brenner, Karl-Heinz (Journal of the Optical Society of America. A, Optics, image science, and vision, 2010)
In this paper, we extend the scalar wave propagation method (WPM) to vector fields. The WPM [Appl. Opt.32, 4984 (1993)] was introduced in order to overcome the major limitations of the beam propagation method (BPM). With the WPM, the range of application can be extended from the simulation of waveguides to simulation of other optical elements like lenses, prisms and gratings. In that reference it was demonstrated that the wave propagation scheme provides valid results for propagation angles up to 85° and that it is not limited to small index variations in the axis of propagation. Here, we extend the WPM to three-dimensional vectorial fields (VWPMs) by considering the polarization dependent Fresnel coefficients for transmission in each propagation step. The continuity of the electric field is maintained in all three dimensions by an enhanced propagation vector and the transfer matrix. We verify the validity of the method by transmission through a prism and by comparison with the focal distribution from vectorial Debye theory. Furthermore, a two-dimensional grating is simulated and compared with the results from three-dimensional RCWA. Especially for 3D problems, the runtime of the VWPM exhibits special advantage over the RCWA.
Gesehen am 07.03.2023